Design of an instrumented bicycle for the evaluation of bicycle dynamics and its relation with the cyclist's comfort - Vanwallleghem, J.; Mortier, F.; de Baere, I.; Loccufier, M.; van Paepegem, W. (Procedia Engineering, 2012)
Next to weight reduction and stiffness increase, increasing the cyclist's comfort has become an additional aspect in the design process of racing bicycles. Several attempts have been made to increase the shock absorption and damping capacity of a racing bicycle, but for the designer it is difficult to estimate the effect on the riding quality of the bicycle and whether the comfort perception of the cyclist increases. This work proposes an experimental test setup for quantifying comfort during outdoor field testing including real time data acquisition and storage from 16 sensors. This data is analysed by means of the whole-body and hand-arm vibration method and the absorbed power method. The initial test results show that the absorbed power method seems to correlate best with the cyclist's comfort. This method does not take acceleration data into account (as in the whole-body and hand-arm vibration method), but the combination of contact force and contact velocity is used for analysis.